Zack's Alligator - Mozelle, Shirley; Watts, James, 1955- (New York : Harper & Row, 1989)
When Zack soaks his new alligator keychain in water, it grows into a full-sized and fun-loving alligator.
"ages 4 to 8"--Jacket.
Keywords: Alligators; Juvenile fiction; Early chapter